Evaluating the post-fire natural regeneration of Mediterranean-type scrublands in Central Spain - Magaña Ugarte, Rosina; Redondo, María Manuela; Sánchez-Mata, Daniel (Mediterranean Botany, 2021)
We performed a five-year assessment of the natural vegetation restoration capacity following the 2012 fires in Valdemaqueda (Madrid, Spain) via the characterization of the post-fire and residual vegetation and the analysis of soil physico-chemical characteristics. Six pilot-plots were established in the affected site. Forest species, representative of the potential natural vegetation of the area (Juniperus oxycedrus subsp. lagunae and Quercus rotundifolia woodlands) and broom shrubs (Cytisus scoparius, Retama sphaerocarpa) were planted to assess the relationship among the stages of ecological succession, competition, and soil restoration processes following devastating fire events. The fire-driven alteration of the soil’s physico-chemical properties was evident, given the increased pH and reduced C/N ratio in the first years of the study. However, we observed an increased soil enrichment in the last years of study, accompanied by the propagation of herbaceous species, su[1]pporting our seed bank findings, showing a clear difference in the sprouting rate between burnt and control plots (80% vs. 20%, respectively). The establishment of robust, pyrophyte shrub species (Cistus ladanifer, C. laurifolius, Rosmarinus officinalis) rather than natural succession evidenced the clear conversion of the vegetation in burnt areas. These findings in the pilot-plots allowed evidencing the high vulnerability of the natural vegetation to the settling of pyrophytes, given their low survival rate under the strong competitive pressure of these pyrophytic species. The proliferation of these pyrophytes could translate into changes in soil macro- and microbiota, nutrient dynamics, species diversity, and interaction, added to the alteration of fire regimes in the area. Overall, these results highlight the risk for soil impoverishment and possible erosion of the fire-affected sites. Moreover, they underline the importance of the establishment and regeneration of Genisteae species to outcompete pioneer pyrophytic species, favoring the restoration of the area’s potential natural vegetation